Effect of dimethyl fumarate on heme oxygenase-1 expression in experimental allergic encephalomyelitis in rats - Kasarełło, Kaja; Jesion, Anika; Tyszkowska, Karolina; Matusik, Katarzyna; Czarzasta, Katarzyna; Wrzesień, Robert; Cudnoch-Jedrzejewska, Agnieszka (Folia Neuropathologica, 2017)
Multiple sclerosis (MS) is an autoimmunological disease leading to neurodegeneration. The etiology of the disease remains unknown, which strongly impedes the development of effective therapy. Most MS treatments focus on modulating the activity of the immune system. Dimethyl fumarate (DMF) exerts a broad spectrum of action, such as modulating immune cell differentiation towards anti-inflammatory subtypes, influencing cytokine production, regulating immune cell migration into the central nervous system, and activating intracellular antioxidant mechanisms. It is well established that activation of the nuclear factor E2 (Nrf2)-dependent pathway, leading to expression of the second-phase antioxidant enzymes, is influenced by DMF. In our experiments we used female Lewis rats in an animal model of MS – experimental allergic encephalomyelitis (EAE). The rats were fed with dimethyl fumarate to test the expression of heme oxygenase-1 (HO-1), one of the second-phase antioxidant enzymes, at specific time points of the symptomatic phases of the disease: on the first day of the occurrence of clinical symptoms (10th day post immunization, DPI); at the peak of clinical symptoms (14th DPI); and at the end of the relapse (21st DPI). The results showed that HO-1 expression, at both the mRNA and protein level, is influenced by DMF administration only at the very beginning of the symptomatic phase of EAE, and not at the peak of clinical symptoms, nor at the end of the relapse. This indicates that the regulation of the Nrf2-dependent antioxidant pathway by DMF occurs at a certain time interval (early EAE/MS) and strongly underlines the importance of the earliest introduction of the therapy to the patient.